Guarantees of the General Authority for Monitoring the Allocation of Federal imports - Abdel Ali Abdel Reda , Hawraa; Zaki Nouri, Assist. Prof. Soha (Basra studies journal, 2022)
The General Authority for Monitoring the Allocation of Federal Revenues is one of the independent bodies stipulated in the Constitution of the Republic of Iraq for the year 2005 in Article (106) of it. Because federal imports are development plans, and because there are important and sensitive specializations that need expertise in economic fields that none of the three bodies can undertake. Its establishment, and in order for it not to depart from the legal frameworks of its existence, and to ensure that the three authorities are not tyrannical when supervising them, they need a set of guarantees and the exclusion of all political influences that could affect its oversight work and the provision of impartiality to carry out its work with the presence of cooperation with the rest of the authorities and that these guarantees differ and vary for that We divided the research into four demands. We dealt with the first requirement for legislative guarantees, the second requirement for political control represented by the legislative authority, the third requirement for administrative control, and the fourth requirement for judicial authority oversight.